2019
DOI: 10.1002/ajoc.201800693
|View full text |Cite
|
Sign up to set email alerts
|

Tin‐Mediated One‐Pot Preparation of β‐Trifluoromethyl‐β acylhydrazonyl Carbonyl Compounds

Abstract: A concise and efficient protocol for the preparation of β‐trifluoromethyl‐β‐acylhydrazonyl carbonyl compounds was developed from multicomponent one‐pot reactions of trifluoroacetaldehyde methyl hemiacetal, acylhydrazines and 2‐bromocarbonyl compounds in the presence of tin powder. The reactions can be carried out under mild reaction conditions to give the products in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Inspired by previous accounts and this work [92,93], Hu et al explored 1,2-nucleophilic addition reactions of trifluoromethylated acylhydrazones with organometallic reagents for the synthesis of trifluorinated homoallylic acylhydrazines [94][95][96][97][98], trifluorinated α-methylene-γ-lactams [99,100], and β-trifluoromethyl-β-acylhydrazonyl carbonyl compounds [101] (Scheme 15). Among these fluorinated products, the trifluoromethylated homoallylic acylhydrazines were easily transformed to CF 3 - substituted pyrazolines and 1,6-dihydropyridazines via a cascade oxidation/cyclization with NXS or Cu(OAc) 2 .…”
Section: Trifluoromethylated Acylhydrazonoesmentioning
confidence: 99%
“…Inspired by previous accounts and this work [92,93], Hu et al explored 1,2-nucleophilic addition reactions of trifluoromethylated acylhydrazones with organometallic reagents for the synthesis of trifluorinated homoallylic acylhydrazines [94][95][96][97][98], trifluorinated α-methylene-γ-lactams [99,100], and β-trifluoromethyl-β-acylhydrazonyl carbonyl compounds [101] (Scheme 15). Among these fluorinated products, the trifluoromethylated homoallylic acylhydrazines were easily transformed to CF 3 - substituted pyrazolines and 1,6-dihydropyridazines via a cascade oxidation/cyclization with NXS or Cu(OAc) 2 .…”
Section: Trifluoromethylated Acylhydrazonoesmentioning
confidence: 99%
“…Our research group recently focused on developing versatile trifluoromethyl building blocks for construction of nitrogen-containing trifluoromethylated compounds . Our previous reports indicated that trifluoromethylated homoallylic N -acylhydrazines 1 underwent a novel cascade oxidation/halogeno­amino­cyclization reaction to give CF 3 -substituted pyrazolines in the presence of NXS (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%